2019
DOI: 10.1126/science.aax1033
|View full text |Cite
|
Sign up to set email alerts
|

Substrate processing by the Cdc48 ATPase complex is initiated by ubiquitin unfolding

Abstract: The Cdc48 adenosine triphosphatase (ATPase) (p97 or valosin-containing protein in mammals) and its cofactor Ufd1/Npl4 extract polyubiquitinated proteins from membranes or macromolecular complexes for subsequent degradation by the proteasome. How Cdc48 processes its diverse and often well-folded substrates is unclear. Here, we report cryo–electron microscopy structures of the Cdc48 ATPase in complex with Ufd1/Npl4 and polyubiquitinated substrate. The structures show that the Cdc48 complex initiates substrate pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
402
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(441 citation statements)
references
References 64 publications
39
402
0
Order By: Relevance
“…4a). Recently, the cryo-EM structure of yeast Cdc48 in complex with Npl4/Ufd1 and K48-linked polyubiquitinated Eos showed that an unfolded ubiquitin moiety binds in the groove of Npl4 and extends all the way into the pore of Cdc48 in the 7 absence of ATP hydrolysis 5 . By contrast, none of the states showed any density in the groove of Npl4 ( Fig.…”
Section: Seesaw Motion Of Npl4 Is Important For the Unfolding Activitmentioning
confidence: 99%
See 1 more Smart Citation
“…4a). Recently, the cryo-EM structure of yeast Cdc48 in complex with Npl4/Ufd1 and K48-linked polyubiquitinated Eos showed that an unfolded ubiquitin moiety binds in the groove of Npl4 and extends all the way into the pore of Cdc48 in the 7 absence of ATP hydrolysis 5 . By contrast, none of the states showed any density in the groove of Npl4 ( Fig.…”
Section: Seesaw Motion Of Npl4 Is Important For the Unfolding Activitmentioning
confidence: 99%
“…Furthermore, we revealed that the disulfiram derivative bis-(diethyldithiocarbamate)-copper (CuET) inhibits the unfolding activity of p97 and locks the conformational changes between p97 and Npl4/Ufd1 by releasing cupric ions under oxidative conditions. 5…”
Section: Introductionmentioning
confidence: 99%
“…Our structural analysis reveals that TgMcrB AAA forms an asymmetric hexamer, similar to the architecture adopted by many other AAA+ family proteins (de la Pena et al, 2018; Enemark and Joshua-Tor, 2006; Gates et al, 2017; Puchades et al, 2017; Ripstein et al, 2017; Twomey et al, 2019; Zehr et al, 2017; Zhao et al, 2015). Asymmetry appears to be maintained by the conformation of key interface residues – Arg360, Glu527 and Tyr530 in one monomer and Arg414, Asp420 and Arg424 in its neighbor – acting in trans .…”
Section: Discussionmentioning
confidence: 52%
“…Numerous biochemical studies have demonstrated the role of an unstructured initiation or engagement region [17][18][19] , yet a substantial fraction of cellular proteasomal substrates appear to lack such flexible segments 20 , begging the question of how their degradation is initiated. While other unfoldases, like Cdc48/p97 may generate disordered regions 21,23,38 , it is also possible that for some proteins ubiquitin-mediated conformational changes are sufficient to expose the obligate unstructured segments. To test this hypothesis, we poly-ubiquitinated our panel of single-lysine barstar variants (Ubn-barstar) and assayed the proteasome's ability to recognize these substrates via its endogenous ubiquitin receptors and degrade them in an ATP-dependent manner (Fig.…”
Section: Substrate Ubiquitination Can Induce a Proteasome-engageable mentioning
confidence: 99%